Pressure treatment enables white-light emission in Zn-IPA MOF via asymmetrical metal-ligand chelate coordination - Qing Yang; Weibin Wang; Yunfeng Yang; Pengyuan Li; Xinyi Yang; Fuquan Bai; Bo Zou (Nature Communications)
Abstract Metal-organic frameworks that feature hybrid fluorescence and phosphorescence offer unique advantages in white-emitting communities based on their multiple emission centers and high exciton utilization. However, it poses a substantial challenge to realize superior white-light emission in single-component metal-organic frameworks without encapsulating varying chromophores or integrating multiple phosphor subunits. Here, we achieve a high-performance white-light emission with photoluminescence quantum yield of 81.3% via boosting triplet excitons distribution through pressure treatment in single-component Zn-IPA metal-organic frameworks. A novel metal-ligand asymmetrical chelate coordination is successfully integrated into the Zn-IPA after a high-pressure treatment over ~20.0 GPa. This modification unexpectedly endows the targeted sample with a new emergent electronic state to narrow the singlet-triplet energy gap, which effectively accelerates the spin-flipping process for boosted triplet excitons population. Time delay phosphor-converted light-emitting diodes are fabricated with long emission time up to ~7 s after switching off, providing significant advancements for white-light and time-delay lighting applications.